Rivaroxaban-Associated Intraparenchymal Hemorrhage Managed with 4-Factor Prothrombin Complex Concentrate - Patel, Jayme S. K.; Rahbar, Aryan J.; Patel, Ketan; Sigal, Tiffany W. (Current emergency and hospital medicine reports, 2018)
Purpose of Review Background: Rivaroxaban is a Xa inhibitor and one of the direct acting oral anticoagulants (DOAC) that currently does not have evidence-based guidelines for its reversal. Prothrombin complex concentrate (PCC) has been recommended as a potential reversal agent for life-threatening bleeds. With no direct antidote and its widespread usage, the attempt to manage life-threatening hemorrhages with procoagulant drugs will continue to rise. Recent Findings Case report :A 55-year-old male on rivaroxaban and clopidogrel presented to another facility with ataxia, confusion, and lateralizing weakness. Computed tomography (CT) scan of the brain showed a large intraparenchymal hemorrhage. He was intubated, given mannitol and nicardipine, and transferred to our tertiary care facility. His coagulation studies upon arrival were normal. He was given 50 units/kg of PCC in an attempt to reverse rivaroxaban and one unit of platelets for clopidogrel reversal. A repeat CT 18 h later showed extension of the bleed. Neurosurgical intervention was not done, and 4 days into his stay, a right cephalic vein thrombosis was found. During his hospital stay, the patient developed encephalopathy and required a tracheostomy tube and gastrostomy tube. A CT on day 36 showed stabilization of the bleeds, and on day 42, he was transferred to a skilled nursing facility. Summary Why should an emergency physician be aware of this? Novel oral anticoagulants are becoming ever popular due to their ease in management and lack of required monitoring when compared to conventional therapy. But, they are still associated with hemorrhages, which is their most common complication. Due to the lack of antidotes and reversal agents for DOACs, prothrombotic agents are being frequently utilized in the setting of life-threatening hemorrhages. While various case reports have been published on the usage of varying dosages of PCC to treat rivaroxaban-associated bleeds, no strong evidence exists to its clinical efficacy. Our case adds to the growing body of evidence showing a lack of clinical efficacy in the reversal of the anticoagulation effects of oral factor Xa inhibitors in addition to a complication in utilizing this potential reversal agent (J Crit Care 33:252–6, 2016; J Thromb Heamost 12:1428–1436, 2014; World Neurosurg 84(6)1956–1961, 2015)